Evolutionary growth theory - Giovanni Dosi; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
This work presents the evolutionary growth theory, which studies the drivers and patterns of technological change and production together with the (imperfect) mechanisms of coordination among a multitude of firms. This requires to studies economies as complex evolving systems, i.e. as ecologies populated by heterogenous agents whose out-of-equilibrium local market interactions lead to the emergence of some collective order at higher level of aggregation, while the system continuously evolves. Accordingly a multi-country multi-industry agent-based model is introduced, where the restless competition of firms in international markets lead to the emergence of growth and persistent income divergence among countries. Moreover, each economy experiences a structural transformation of its productive structure during the development process. Such dynamics results from firm-level virtuous (or vicious) cycles between knowledge accumulation, trade performances, and growth dynamics. The model also accounts for a rich ensemble of empirical regularities at macro, meso and micro levels of aggregation. Finally, the model is employed to assess different strategies that laggard countries can adopt to catch up with leaders. Results show that in absence of government interventions, laggards will continue to fall behind. On the contrary, industrial policies can successfully drive international convergence among countries.
Keywords: F41; F43; O4; O3; 330; Endogenous growth; structural change; technology-gaps; industrial policies; evolutionary economics; agent-based models